Elemente einer Soziolinguistik Nordafrikas - Wolff, H Ekkehard (Stellenbosch Papers in Linguistics Plus, 2012)
The sociolinguistics of the Northern African states is relatively obscure in terms of internationalresearch, since these regions do not feature significantly in the areas of Arabic studies/Orientalism,Romance studies or classical African studies. A similar problem holds for the scientific classificationof studies on Berber. This article develops an africanist-sociolinguistic approach to central questionsrefering to multilingualism in the context of historically unfolding geo- and sociolinguistic profiles ofNorthern African nations. This will be discussed within the framework of a historical linguisticstratigraphy. The article broadens the concept of diglossia as used in the arabophonic context in orderto include a multilingual dimension (polyglotism), and discusses models of conflict avoidancebetween native speakers of Arabic, Berber and French, respectively. The article focuses onsituationally adequate language political arrangements, especially in the area of education, on the basisof L1-based additive bi- and trilingualism models.Keywords: Schlüsselbegriffe : Afrikanistik, Arabisch, Berber, Bildung, Diglossie, Französisch, Maghreb,Mehrsprachigkeit, Polyglossie, Soziolinguistik, SprachenpolitikAfrican studies, Arabic, Berber, education, diglossia, French, Maghreb, multilingualism,polyglotism, sociolinguistics, language policy